Disability and Children as Begging Guides: For how Long Shall Children be Used as Begging Guides by Visually Impaired Persons in Africa? - Agunyai, Samuel Chukwudi; Ojakorotu, Victor (Journal of Intellectual Disability - Diagnosis and Treatment, 2021)
This study examines the effect of using children as begging guides by people with sensory disabilities in Africa. It argues that in some African countries, visually impaired persons, especially parents and relatives, have devised the strategy of abusing their children or someone very close to them as begging guides for financial gain. While this strategy has remained a recurrent problem with severe social, economic, political, and legal implications, scientific research on addressing these implications is scarce. Given this, the article examines the rationale for using children as begging guides, its effects on the children and visually impaired parents, and mitigation strategies against abuse of children as begging guides in Africa. The qualitative research design based on key informant interviews (KIIs) complemented social exclusion and childhood theoretical underpinnings of the study. Results from (KIIs) showed that poverty, religion, cultural beliefs, financial profiteering, poor governance, breakdown in policy implementation against begging are among the rationale why children are abused and used as begging guides. The results also showed that these children experience low academic performance in school, harassment, psychological trauma, health complications from laborious trekking. At the same time, their visually impaired parents suffer from regrets and guilt of not being able to provide good parental care to their children. It concludes that good rehabilitation, vocational programmes, and prompt government supports for people with sensory disabilities would lessen the abuse and use of children as begging guides in Africa.